An Anatomical and Radiographic Study on the Vertebral Column of the Two-Toed Sloth (Choloepus hoffmanni) - Chinchilla-Barboza, Maripaz (2021)
The Choloepus Hoffmani is a mammal belonging to the Xenarthra superorder; xenarthrans are distributed from North to South America. It is common for these animals to require medical attention at wildlife rescue centers after being attacked by domestic animals or run over by cars. A proper understanding of this species’ anatomy is vital in order to be able to offer them a proper level of clinical attention. This publication aims to describe the spine’s anatomical and radiographic characteristics of the Choloepus Hoffmani. Four individuals were used in this research; the spine bones were cleaned by boiling and maceration. In the results, it was possible to observe how the postcranial axial skeleton in the sloths is made up by five of distinctive vertebra types. In the spine were found: six cervical vertebrae, a variable number of thoracic vertebrae, xenarthrous lumbar vertebrae, and a fusion between the sacrum and coxal bone. Finally, four underdeveloped caudal vertebrae were also identified in a small stump-like tail. Radiographically, no pathologies were observed in the alignment or structure of the spine. In conclusion, the present study described both the osteology alongside the anatomical radiography of the vertebral column of the Choloepus hoffmani, highlighting the particularities that are not found in domestic mammals and other members of the Xenarthra superorder. Information of this kind is relevant for forensic wildlife analysis, alongside aiding the treatment of animals in this species who suffered lesions in their spine.